Consumer Complaint Behavior (CCB) of Jombang Health Card (KJS) for increasing health facility service - Endah Sulistyowati; Danny Wibowo (Journal of Economics, Business, and Accountancy Ventura, 2015)
The purpose of this study is to see and assess why they complaint, how to make complaints and alternative for patients complain KJS (Jombang Health Card) users, as such information from various forms of complaint can be used to improve health care strategy hospital. This is an exploratory and qualitative research using Focus Group Discussion (FGD) towards 20 people. It was found that the reason KJS users complain services is due to factors that include poor service, poor facilities, the be-ginning of a long process and product factors include: the availability of drugs, limited room space and time limits hospitalization. The second factor is a fatal loss, allowing participants to have a longer hierarchy levels due to passing through a more complicated procedure. Complaints and personality types of participants affect the nature of the expectations expressed through the submission of a complaint. The results include the results of the settlement of complaints received by the partici-pants, and satisfaction evaluation with the settlement. Generally poor service stimu-lates participants to convey a simple complaint in connection with suggestions or criticism to improve services and hospital management.